Pengaruh Gaji dan Budaya Organisasi terhadap Motivasi Kerja Karyawan pada PT Daewoo Securities Indonesia - B Say, Alfonsus (Journal of Economics & Business UBS, 2020)
The study aims to analyze checklists verifying initial review of the compensation system, as prayer one factor to review giving motivation on employees, because in stock company employees are praying one kalbe that paled productive. For the data collected by research using descriptive method. The data collected Used study is documentation, observation and questionnaires and using the help of SPSS 22.0 for review of test Validation and Reliability. Research results show that the findings of the two variable regression testing between Salaries and organizational culture as well as significant influence on employee motivation. As well as very important ritual activity in socialize and internalization of cultural values.